The Effect Of Word Search Strategy By Using Scrabble As The Media On The Students’ Achievement In Vocabulary - Reni Deliani Fahwi (Universitas Muhammadiyah Sumatera Utara, 2022)
This research was carried out to investigate the students’ achievements in vocabulary used Word Search Strategy by Using Scrabble as the Media. The research was to find out the effect of Word Search Strategy by Using Scrabble as the Media on the Students’ Achievement in Vocabulary. This research was conducted at SMP Cerdas Murni at Beringin street number 33. Tembung, Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara. The sample consisted of 80 students which were taken by purposive sampling technique and divided into two different groups namely experimental and control groups. Multiple choice test was used as instrument which consisted of twenty questions in pre-test and post-test. Based on the data analysis, the result showed that there was significant effect of word search strategy by using scrabble in the students’ achievement with t-critical (tc) value was higher than ttable on the level 8.8810 2.024. Therefore, the alternative hypothesis ( Ha ) was accepted and the null hypothesis was rejected. So, it means that applying of word search strategy by using scrabble as the media on the students’ achievement was effective.